Some Problems on the Making of Mathematical Modelling of a Profit-Loss Sharing Scheme Using Data Simulation - Novriana Sumarti; Kuntjoro Adji Sidarto; Muhammad Syamsuddin; Vina Fitriyani Mardiyyah; Abu Rizal (Institute for Research and Community Services (LPPM) ITB, 2015)
The mathematical model for a profit-loss sharing scheme is formulated in order to see how this scheme can replace the traditional practice of lending money against high interest by usurers. It is sourced from the musyarakah method in Islamic Syariah law and implemented for small-scale investments of traditional-market traders. They are the common target of usurers, so they may end up poorer than they were before. The main goal of the model is to find the appropriate portion of profit share, so the investment is profitable not only for the investor but also for the trader. There are three main problems in the process of formulating the mathematical model and finding optimized results. The first problem is providing the appropriate amount of data to be implemented in the model. The second problem is determining the objective function for the optimization of the portion of profit share. The last problem is determining the appropriate values of the parameters for certain types of traders. We found a significant result in determining the appropriate values of the parameters that explain the potential capability of the traders in handling larger amounts of capital to be invested in order to achieve our main goal.